(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2015)
In the framework of the public consultation launched on the occasion of the tenth anniversary of the entry into force of the Council Regulation (EC) No 139/2004, on the control of concentrations between undertakings, the debate on the need to regulate the treatment of minority shareholdings which do not confer control has been resumed. The European Commission faces the challenge to define a reform to give an answer to the need to catch transactions that may significantly affect effective competition but, at the same time, to refrain from imposing disproportionate burdens on undertakings.